PEMBERDAYAAN MASYARAKAT MELALUI PENINGKATAN KETERAMPILAN WANITA BERBASIS POTENSI ALAM LOKAL DI DESA PUNGGUR BESAR, KUBU RAYA - Edy Suryadi (Jurnal Buletin Al-Ribaath, 2016)
The village of Punggur Besar is located in the district of area sei Kakap, Kubu Raya, West Kalimantan Province which has an area of the village of 56.322 hectares square is divided into several sections including: Settlements 5.970 ha, Field 24.966 ha, Plantation 17.800 ha, land Agriculture 6.940 ha, 330 ha of irrigated agricultural land, marshes 316 ha. People in the village of Punggur Besar has potential in agriculture. Many natural potential contained in Punggur Besar village, people in the village do not have the knowledge checkers skills to manage and exploit the potential of the local nature of the village. Therefore we selected Punggur Besar village as village built by providing skills in exploiting the potential of the local in the village in order to increase the income of local communities in addition we will also provide knowledge about ways to marketing they products as well as the feasibility analysis. The formulation of the problem in this activity is the "Community Empowerment through Skill-Based Natural Potential of Local Women In the village of Sungai Kakap Punggur Kabupaten Kubu Raya"Keywords: Agricultural, Economics, Entrepreneurship, Sustainable Independent Community